Significance of cultural and historical resources in development of discovering tourism (case of Volodymyr-Volynskyi district of Volyn region) - Iryna Netrobchuk (Časopis Socìalʹno-Ekonomìčnoï Geografìï, 2016)
Twenty attractive historical places are located in Volyn region. They have preserved many monuments of architecture, archeology and history both local and national importance. Volodymyr-Volynskyi district is worthy to be noted among others with many interesting historical inhabited places, historical and cultural objects of the period of Kievan Rus’. On state registration there are 103 objects of cultural heritage (including 20 of national importance). 46 out of 103 are historical monuments (including 2 of national importance), 4 archeological sites, 48 architectural and urban planning (including 18 - of national importance), 3 monuments of monumental art and one monument of landscape art in the Volodymyr-Volynskyi district. There is the State historical and cultural reserve “Ancient Volodymyr” in the city. Tourist image of the area is determined primarily by the presence of cultural and historical resources that can be used in tourism.